Clinical and dermatoscopic characteristics of lichen planus‐like keratosis in a West‐Asian population. (17th November 2020) - Ansari, Mahshid Sadat; Akay, Bengu Nisa; Cengiz, Fatma Pelin; Rosendahl, Nikita; Mahmoudi, Hamidreza; Daneshpazhooh, Maryam; Rosendahl, Cliff
Abstract: Background/Objective: The clinical and dermatoscopic features of lichen planus‐like keratosis have been described but the characteristics of this entity in a West‐Asian population are not known. Methods: We retrospectively analysed 82 histopathologically verified cases of lichen planus‐like keratosis from 81 patients from Iran and Turkey. Results: The majority of lichen planus‐like keratoses were macules (61% n  = 50), clinically pigmented (67.1% n  = 55) and dermatoscopically multi‐coloured (91.5% n  = 75). The majority (63.4%) had a single dermatoscopic pattern, most frequently: structureless (35.4%), dots (14.6%) and angulated lines (8.5%). Of the lesions with more than one pattern ( n  = 30), the majority ( n  = 21) had asymmetry of pattern, the most common combinations being structureless plus dots ( n  = 8) and structureless plus angulated lines ( n  = 5). The most common structure was pigmented dots, most frequently grey and present in 70.7% of cases. Vessels were seen in 30.5% of lesions, being significantly more prevalent in non‐pigmented, than pigmented, lichen planus‐like keratoses (83.3% vs. 21.4% P < 0.001 ). When we compared lichen planus‐like keratosis in the current study to that entity in a large North American study, the statistically significant differences in a West‐Asian population included a greater frequency of pigmented variants, a lower incidence in females and a lower prevalence on the torso, in favour of the face. Conclusions: Lichen planus‐like keratosis in a West‐Asian population has clinical and dermatoscopic similarities to that entity in another studied population. The significant differences in gender association and anatomical site may be secondary to cultural factors.